The variable X-ray spectrum of Markarian 766 - I. Principal components analysis - Miller, L; Turner, T; Reeves, J; George, I; Kraemer, S; Wingert, B (2006)
Aims: We analyse a long XMM-Newton spectrum of the narrow-line Seyfert 1 galaxy Mrk 766, using the marked spectral variability on timescales >20ks to separate components in the X-ray spectrum. Methods: Principal components analysis is used to identify distinct emission components in the X-ray spectrum, possible alternative physical models for those components are then compared statistically. Results: The source spectral variability is well-explained by additive variations, with smaller extra contributions most likely arising from variable absorption. The principal varying component, eigenvector one, is found to have a steep (photon index 2.4) power-law shape, affected by a low column of ionised absorption that leads to the appearance of a soft excess. Eigenvector one varies by a factor 10 in amplitude on time-scales of days and appears to have broad ionised Fe K-alpha emission associated with it: the width of the ionised line is consistent with an origin at about 100 gravitational radii. There is also a strong component of near-constant emission that dominates in the low state, whose spectrum is extremely hard above 1 keV, with a soft excess at lower energies, and with a strong edge at Fe K but remarkably little Fe K-alpha emission. Although this component may be explained as relativistically-blurred reflection from the inner accretion disc, we suggest that its spectrum and lack of variability may alternatively be explained as either (i) ionised reflection from an extended region, possibly a disc wind, or (ii) a signature of absorption by a disc wind with a variable covering fraction. Absorption features in the low state may indicate the presence of an outflow.